Real‐time reconstruction of pipes using RGB‐D cameras - Kim, Dong‐Min; Ahn, JeongHyeon; Kim, Seung‐wook; Lee, Jongmin; Kim, Myungho; Han, JungHyun (Computer animation and virtual worlds, 2024)
This paper presents a novel method that automatically reconstructs pipes in real time using an RGB‐D camera. The input image is decomposed into superpixels, and a pipe element, which is a 3D circle lying on the pipe surface, is generated for each superpixel. Over frames, the pipe elements are grouped into sequences and are finally modeled in parametric equations. The method is tested in daily settings, where the pipes may be curved and their radii may vary along the axes. The test results show that the method is able to reconstruct pipes efficiently, precisely and robustly. In this paper, we present a novel method that automatically reconstructs 3D pipes in real time using an RGB‐D camera. The method is capable of reconstructing curved pipes composed of linear and circular segments and generating their corresponding parametric equations.